Growth dynamics and light scattering of gold nanoparticles in situ synthesized at high concentration in thin polymer films - Guyot, Corentin; Vandestrick, Philippe; Marenne, Ingrid; Deparis, Olivier; Voué, Michel (Beilstein Journal of Nanotechnology, 2019)
Background: Numerous optical applications of nano-objects require a dispersion of the nanoparticles in a dielectric matrix. In order to achieve high particle concentrations, one can, as an alternative, directly grow the particles in a polymer or an inorganic film by, e.g., thermal annealing.Results: Simple laser reflection experiments showed that this growth process induced light scattering at the film/air interface. We report on this phenomenon, considering the growth dynamics of gold nanoparticles in a polymer film. The scattering of light was studied by measuring the bi-directional reflection distribution function. In parallel with the observation of enhanced scattering, imaging ellipsometry in dynamics mode showed that local values of the ellipsometric angles Ψ and Δ were strongly modified by the annealing process.Conclusion: A diffraction pattern corresponding to local modifications of the optical properties of the film gradually appeared, which turned out to be the signature of the growth of the Au nanoparticles. Moreover, the monitoring of the statistical distribution of the ellipsometric angles during annealing helped evidencing two regimes in the dynamics of the nanoparticle growth and in the optical response of the nanocomposite.
Keywords: gold; imaging ellipsometry; metal nanoparticles; plasmonic nanocomposite; polymer films

Polymer Films with Embedded Metal Nanoparticles - Heilmann, A. (Springer, 2003)

Optical Properties of Metal Clusters - Kreibig, U.; Vollmer, M. (Springer Berlin, 1995)

(untitled) - Chowdhury, H.; Xu, X.; Huynh, P.; Cortie, M. B. (J. Sol. Energy Eng., 2005)

(untitled) - Xu, X.; Stevens, M.; Cortie, M. B. (Chem. Mater., 2004)

(untitled) - Yin, J.; Feng, G.; Zhou, S.; Zhang, H.; Wang, S.; Zhang, H. (J. Mod. Opt., 2016)

(untitled) - Meng, X.; Fujita, K.; Moriguchi, Y.; Zong, Y.; Tanaka, K. (Adv. Opt. Mater., 2013)

(untitled) - Kim, M.-J.; Na, H.-J.; Lee, K. C.; Yoo, E. A.; Lee, M. (J. Mater. Chem., 2003)

(untitled) - Compton, D.; Cornish, L.; van der Lingen, E. (Gold Bull., 2003)

(untitled) - Cattaruzza, E.; Battaglin, G.; Gonella, F.; Polloni, R.; Scremin, B.; Mattei, G.; Mazzoldi, P.; Sada, C. (Appl. Surf. Sci., 2007)

(untitled) - Daniel, M.-C.; Astruc, D. (Chem. Rev., 2004)

(untitled) - Elghanian, R.; Storhoff, J. J.; Mucic, R. C.; Letsinger, R. L.; Mirkin, C. A. (Science, 1997)

(untitled) - Zhang, J.; Wang, L.; Pan, D.; Song, S.; Boey, F. Y. C.; Zhang, H.; Fan, C. (Small, 2008)

(untitled) - De Boni, L.; Wood, E. L.; Toro, C.; Hernandez, F. E. (Plasmonics, 2008)

(untitled) - Jiang, T.; Xu, Y.; Tian, Q.; Liu, L.; Kang, Z.; Yang, R.; Qin, G.; Qin, W. (Appl. Phys. Lett., 2012)

(untitled) - Wu, D.; Peng, J.; Cai, Z.; Weng, J.; Luo, Z.; Chen, N.; Xu, H. (Opt. Express, 2015)

(untitled) - Kang, Z.; Guo, X.; Jia, Z.; Xu, Y.; Liu, L.; Zhao, D.; Qin, G.; Qin, W. (Opt. Mater. Express, 2013)

(untitled) - Jiang, T.; Kang, Z.; Qin, G.; Zhou, J.; Qin, W. (Opt. Express, 2013)

(untitled) - Liao, H. B.; Xiao, R. F.; Fu, J. S.; Yu, P.; Wong, G. K. L.; Sheng, P. (Appl. Phys. Lett., 1997)

(untitled) - Varnavski, O. P.; Goodson, T.; Mohamed, M. B.; El-Sayed, M. A. (Phys. Rev. B, 2005)

(untitled) - Sun, C.; Qu, R.; Ji, C.; Meng, Y.; Wang, C.; Sun, Y.; Qi, L. (J. Nanopart. Res., 2009)

(untitled) - Hariprasad, E.; Radhakrishnan, T. P. (Chem. – Eur. J., 2010)

Nanocomposites: In Situ Synthesis of Polymer-Embedded Nanostructures - Hariprasad, E.; Radhakrishnan, T. P. (Chemistry inside a polymer thin film: in situ soft chemical synthesis of metal nanoparticles and applications, 2013)

(untitled) - Pandit, S.; Kundu, S. (AIP Conf. Proc., 2018)

(untitled) - Banu, K.; Shimura, T. (New J. Chem., 2011)

New way of synthesis of uniform gold nanoparticles for the detection of few molecules - Omar, R. (Université de Lorraine et Université Libanaise, 2017)

Ellipsometry and Polarized Light - Azzam, R. M. A.; Bashara, N. M. (Elsevier Science B.V., 1987)

(untitled) - Fujiwara, H.; Koh, J.; Rovira, P. I.; Collins, R. W. (Phys. Rev. B, 2000)

Ellipsometry at the Nanoscale - Yanguas-Gil, A.; Wormeester, H. (Relationship Between Surface Morphology and Effective Medium Roughness, 2013)

(untitled) - Tsou, C.; Huang, Y. S.; Chang, H. C. (Sens. Mater., 2005)

(untitled) - Toyoda, T.; Yabe, M. (J. Phys. D: Appl. Phys., 1983)

(untitled) - Noorjahan, A.; Choi, P. (Polymer, 2013)

PVC Handbook - Wilkes, C. E.; Summers, J. W.; Daniels, C. A. (Hanser, 2005)

(untitled) - Clémenson, S.; David, L.; Espuche, E. (J. Polym. Sci., Part A: Polym. Chem., 2007)

(untitled) - Keddie, J. L.; Jones, R. A. L.; Cory, R. A. (Europhys. Lett., 1994)

(untitled) - Dahmouchène, N.; Coppée, S.; Voué, M.; De Coninck, J. (Phys. Status Solidi C, 2008)

(untitled) - Voué, M.; Dahmouchène, N.; De Coninck, J. (Thin Solid Films, 2011)

(untitled) - Ramesh, G. V.; Porel, S.; Radhakrishnan, T. P. (Chem. Soc. Rev., 2009)

(untitled) - Bay, A.; Cloetens, P.; Suhonen, H.; Vigneron, J. P. (Opt. Express, 2013)

(untitled) - Necas, D.; Klapetek, P. (Cent. Eur. J. Phys., 2012)